Costa Rica : The World Bank Group Country Opinion Survey FY 2014 - World Bank Group (World Bank, Washington, DC, 2015)
The Country Opinion Survey in Costa Rica assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Costa Rica perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Costa Rica on 1) their views regarding the general environment in Costa Rica; 2) their overall attitudes toward the WBG in Costa Rica; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Costa Rica; and 4) their perceptions of the WBG’s future role in Costa Rica.